Pengaruh Ketersediaan Sarana Mengajar dan Pelatihan Guru Terhadap Kinerja Guru SMA Negeri 1 Sragen - Ayuningtyas, Dhita; , Drs. H. Sabar Narimo, MM. M.Pd (2015)
The purpose of this study was to determine 1) the influence of completeness teaching tool on teacher performance, 2) the impact of teacher training on teacher performance, 3) the effect of the availability of teaching and training on teacher performance. This research is a quantitative research. This study took place in SMA N 1 Sragen. The population in this study were all high school teachers N 1 Sragen which amounts to 82 teachers who take it all because this research is the study population. Data obtained through questionnaires and documentation. The data analysis technique multiple linear regression analysis, F test, t-test, R ^ 2, and the relative contribution and effective. The conclusion of this study were 1) the availability of teaching and a positive impact on teacher performance. It is based on multiple linear regression analysis obtained t_hitung> t_hitung, namely 3.752> 1.292 and 0.000 significance value <0.05. 2) teacher training has positive influence on the performance of teachers. It is based on multiple linear regression analysis obtained t_hitung> t_hitung, namely 2.331> 1.292 and 0.022 significance value <0.05 3) the availability of teaching and teacher training has positive influence on the performance of teachers. This is evidenced by F_hitung> F_tabel, ie 11.272> 3.07 and a significance value 0,000 <0,05 .. 4) variable availability of teaching relative contribution of 69.6% and 15.5% effective contribution and provide teacher training variables the relative contribution of 30.4% and the effective contribution of 6.7%.